Biomineralization and AHLs-guided quorum sensing enhanced phosphorus recovery in the alternating aerobic/anaerobic biofilm system under metal ion stress. (1st January 2023) - Zhang, Hao; Zhang, Shuang-Shuang; Zhang, Wei; Zhu, Liang; Li, Yi-Ping; Pan, Yang
Abstract: The alternating aerobic/anaerobic biofilm system had been applied for phosphorus (P) enrichment and recovery because of the advantage of low energy consumption and high efficiency. The metal ions and N-acyl-L-homoserine lactones (AHLs) in system were studied to better clarify the mechanism of P uptake/release under metal ion stress. The results indicated that the increase of metal ions stimulated the release of AHLs, and AHLs-guided quorum sensing (QS) enhanced P uptake. Moreover, biomineralization could stimulate the increase of P content in biofilm (Pbiofilm ). Meanwhile, some ortho-p was converted to short-chain poly-p in extracellular polymer substance (EPS), and others were transferred into cell through EPS to synthesize poly-p. With the Pbiofilm increased, more P could be absorbed/released due to the shift in the metabolic model of polyphosphate accumulating organisms (PAOs). The release of AHLs between microorganisms was also inhibited when PAOs reached the state of P saturation (75.6 ± 2.5 mg/g SS), which meant that the effect of signaling function would tend to stabilize, and the 169.2 ± 2.6 mg/L P concentration in the enriched solution was obtained due to the P release was inhibited. Moreover, P was rapidly transferred to the new enriched solution after the P was recovered, and PAOs restored its capability of P uptake/release. In addition, 31 P-NMR analysis demonstrated that EPS played a major role in PAOs compared to cell, and inorganic phosphorus (IP) played an essential role in the uptake/release of P compared to organic phosphorus (OP). Furthermore, the microbiological analysis showed that Candidatus Accumulibacter was positively correlated with AHLs (P < 0.05). This study provided essential support for clarifying the P metabolism mechanism of PAOs. Graphical abstract: Image 1 Highlights: The 169.2 mg/L phosphorus concentration was obtained under 200 mg/L COD. The increase of metal ions stimulated the release of AHLs. The AHLs-guided quorum sensing enhanced phosphorus storage of PAOs. Increased phosphorus content in biofilm shifted the metabolic model of PAOs. The HAP and struvite were involved in phosphorus uptake/release process by PAOs.